2001
DOI: 10.4049/jimmunol.167.7.3545
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: STAT Activation By IL-19, IL-20 and mda-7 Through IL-20 Receptor Complexes of Two Types

Abstract: IL-10-related cytokines include IL-20 and IL-22, which induce, respectively, keratinocyte proliferation and acute phase production by hepatocytes, as well as IL-19, melanoma differentiation-associated gene 7, and AK155, three cytokines for which no activity nor receptor complex has been described thus far. Here, we show that mda-7 and IL-19 bind to the previously described IL-20R complex, composed by cytokine receptor family 2–8/IL-20Rα and DIRS1/IL-20Rβ (type I IL-20R). In addition, mda-7 and IL-20, but not I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
358
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(370 citation statements)
references
References 17 publications
10
358
1
1
Order By: Relevance
“…7,10 Studies using keratinocyte-specific STAT3 knockout mice have suggested that STAT3 is essential for keratinocyte migration, and plays a crucial role in skin remodeling, including hair cycle and wound healing. 30 Since STAT3 is the major STAT factor activated by IL-24, 10,12 it is tempting to hypothesize that IL-24 may play a role in epidermal functions and pathogenesis, such as wound healing and inflammation (psoriasis). 7,21 In the process of tumor development, IL-24 may also function as a cytokine to enhance cancer cell survival and growth rather than tumor suppression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,10 Studies using keratinocyte-specific STAT3 knockout mice have suggested that STAT3 is essential for keratinocyte migration, and plays a crucial role in skin remodeling, including hair cycle and wound healing. 30 Since STAT3 is the major STAT factor activated by IL-24, 10,12 it is tempting to hypothesize that IL-24 may play a role in epidermal functions and pathogenesis, such as wound healing and inflammation (psoriasis). 7,21 In the process of tumor development, IL-24 may also function as a cytokine to enhance cancer cell survival and growth rather than tumor suppression.…”
Section: Discussionmentioning
confidence: 99%
“…7 Expression of IL-24 was detected in spleen, thymus, 8 melanocytes, 9 ConA activated human PBMC cells, 10 LPS-treated monocytes and anti-CD3-treated T cells. 11 Two heterodimeric receptors for IL-24 have been identified, IL-20R1/IL-20R2 and IL-22R/IL-20R2, 10,12 the subunits of which belong to the class II cytokine receptor family. 13 IL-24 can bind to the IL-20R2 subunit alone, but co-expression of either IL-20R1 or IL-22R not only increases the binding affinity but also is necessary for receptor activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-20RB associates with IL-20RA to form IL-20RI that binds IL-19, IL20 and IL-24, and IL-20RB associates with IL-22RA1 to form IL-20-RII that binds IL-20 and IL-24. 2,13,[19][20][21] After binding of the different ligands to the receptor complexes, signals are predominantly transducted via Janus kinase-signal transducer and activation of transcription pathways. 22 IL-20-RI is mainly expressed in the skin, lung and reproductive organs as well as in various glands.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of IL-20-RII seems to be more restricted with high levels detectable only in the skin. 2,13,[19][20][21] There are conflicting findings with regard to the expression of IL-20R subunits in skin lesions of psoriasis.…”
Section: Introductionmentioning
confidence: 99%